ANALISIS SISTEM PENDIDIKAN MADRASAH DAN PESANTREN DI INDOESIA: TANTANGAN DAN PELUANG DALAM ERA MODERNISASI (STUDI KASUS DI PON PES HIDAYATUL MUBAROK) - Neila Qonita; Muhammad Nazir; Hidayanti; Romlah; Zainal Arfin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to provide a description of Madrasah and Pesantren Education System Analysis: Challenges and Opportunities in the Era of Modernization. This research was conducted at Hidayatul Mubarok Uman Agung Islamic Boarding School Foundation, Bandar Mataram sub-district, Central Lampung district. This research uses a qualitative approach, namely field research, where data is collected in the field to see phenomena in a natural environment. The data collection methods used in this research are interviews, observation, and documentation. Researchers used the Triangulation technique to test the validity of the data. The results showed that the use of technology at Hidayatul Mubarok Islamic Boarding School Foundation made a positive contribution in supporting the learning process and pesantren management, although there were still some obstacles such as limited infrastructure, human resource readiness, and cultural barriers. With the right strategies, such as improving infrastructure, training human resources, and implementing effective regulations, this pesantren has a great opportunity to optimize technology as an integral part of modern education without putting aside the Islamic values that are its identity.